Poetry and feminine crafts in the letters of the young Marquise of Alorna (1750-1839) - Anastácio, Vanda (2016)
abstract : Taking as a starting point the association between embroidery and language conveyed by the Greek myth of Filomela and Procne, this article examines the relationship between social status and ornaments like embroidery and lace. In order to illustrate this relationship an example is selected form the letters exchanged between the Marquise of Alorna and her Father where a connection is established between the production of these 'feminine' crafts, women's culture and womens writing, in the XVIIIth Century